[Le Corbusier et Pierre Jeanneret. Oeuvre complete 1910 - 1929] - Boesiger, Willy (Zürich : D'Architecture, 1965)
Obras completas 1910-1929
Keywords: LE CORBUSIER; ARQUITECTOS; SUIZA; FRANCIA; JEANNERET, PIERRE